Integrated photonics enabling ultra-wideband fibre–wireless communication - Yunhao Zhang; Haowen Shu; Yijun Guo; Peiqi Zhou; Luyu Wang; Jianyang Cai; Liyuan Yao; Linshan Yang; Linze Li; Tianyu Long; Zhouze Zhang; Changhao Han; et al. (Nature, 2026)
Abstract Telecommunication systems are evolving towards ultrawide bandwidth and low latency, supporting wired and wireless links and their non-blocking interconnection 1 . However, a long-standing bandwidth mismatch between fibre communication and its wireless counterpart arises from fundamental disparities in signal architectures and hardware constraints 2,3 , which prevent high-speed and compatible transmission across the two domains. This challenge further complicates unified system design and hinders the realization of high-throughput-density, congestion-free fibre–wireless links under wideband-access scenarios 4 . Here we present an ultra-wideband (UWB) integrated photonics scheme that facilitates fibre–wireless communication over a shared-bandwidth infrastructure. Built on electro–optic (EO) and optic–electro (OE) conversions featuring 3-dB operational bandwidths exceeding 250 GHz and cross-architecture adaptability, our system demonstrates unprecedented data transmission capabilities in both wired and wireless links. Using the same set of devices and powered by the proposed complex bidirectional gated recurrent unit (complex-biGRU) algorithm, ultrahigh single-lane data rates of 512 Gbps for short-reach fibre and, for the first time to the authors’ knowledge, 400-Gbps high-speed wireless transmission have been achieved. Furthermore, high-density access is enabled by an all-optically assisted ultra-broadband wireless scheme. Real-time multichannel 8K video transmission is successfully demonstrated across 86 channels, seamlessly using a spectral range from 138 to 223 GHz. These findings in unified telecommunication development show the potential for the development of high-speed, densified and low-latency communication networks.